Investigating Knowledge Management Strategies in Central University Libraries in India - P.M., Naushad Ali; Khan, Daud (DESIDOC Journal of Library & Information Technology, 2017)
The aim of this research paper is to investigate the knowledge management strategies adopted by the libraries of central universities in India. Review of literature, reveals that codification and personalisation have been considered knowledge management strategies for sharing explicit and tacit knowledge within the library system. To determine the most used knowledge management strategies in libraries, 14 tools (seven each for codification and personalisation) were recognised from the literature review and taken for examination. A total of 116 library and information science professionals of 23 central universities spread across India were surveyed through a web-based questionnaire to explore the knowledge management strategies followed and data analyses were conducted by using SPSS version 22.0. The findings of the research show that both codification and personalisation have been used in libraries, though the balance of codification and personalisation was not in 80-20 ratio. Between codification and personalisation, codification was found to be the most useful strategy with collective mean difference, i.e., 0.312. This study has practical implications for those who are not fully aware of the prominence of knowledge management and how knowledge management strategies can be used to gain a competitive advantage.